2015
DOI: 10.1016/j.enconman.2015.04.046
|View full text |Cite
|
Sign up to set email alerts
|

Effects of direct injection timing and blending ratio on RCCI combustion with different low reactivity fuels

Abstract: ElsevierBenajes Calvo, JV.; García Martínez, A.; Monsalve Serrano, J. (2015). Effects of direct injection timing and blending ratio on RCCI combustion with different low reactivity fuels. Energy Conversion and Management. 99:193-209. doi:10.1016/j.enconman.2015.04.046. Effects of Direct injection timing and Blending Ratio on RCCI combustion with different Low Reactivity FuelsEnergy Conversion and Management, Volume 99, 2015, Pages 193-209. http://dx.doi.org/10.1016/j.enconman.2015 AbstractThis work investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 154 publications
(79 citation statements)
references
References 34 publications
(30 reference statements)
2
77
0
Order By: Relevance
“…In addition, physicochemical properties of E85 resulted in a particular combustion behavior with narrow operating range, limited by misfire and excessive knocking at low and high load, respectively. By contrast, minor portions of ethanol (10%-20%) showed clear potential to reach EURO VI NOx and soot levels with improved HC and CO emissions from low to high load [38].…”
Section: Homogeneous Charge Compression Ignition (Hcci) a Widely Invmentioning
confidence: 99%
“…In addition, physicochemical properties of E85 resulted in a particular combustion behavior with narrow operating range, limited by misfire and excessive knocking at low and high load, respectively. By contrast, minor portions of ethanol (10%-20%) showed clear potential to reach EURO VI NOx and soot levels with improved HC and CO emissions from low to high load [38].…”
Section: Homogeneous Charge Compression Ignition (Hcci) a Widely Invmentioning
confidence: 99%
“…Thus, several investigations have been conducted with the aim of insight into the RCCI phenomena. First of all, the effects of the gasoline percentage in the blend and direct injection timing were widely studied [25][26] [27]. These works revealed that RCCI concept allows to reach ultra-low NOx and soot emissions levels, together with improved fuel consumption compared to conventional diesel combustion (CDC).…”
Section: Homogeneous Charge Compression Ignition (Hcci) Is a Widely Imentioning
confidence: 99%
“…It was reported that delay in direct injection leads to a two stage heat release since the premixed combustion takes place initially, followed by the diffusion combustion whereas advanced direct injection leads to a single stage heat release [84]. It was reported that by keeping Start of Ignition (SOI) constant around -30° ATDC and increasing the LRF proportion, it improves the ignition delay, whereas keeping SOI around -10 ATDC and increasing the LRF proportion has no significant effects on delayed ignition.…”
Section: Injection Timingmentioning
confidence: 99%